ANTICIPATING DOMESTIC VIOLENCE (KDRT) AGAINST THE LEVEL OF HARMONY IN THE FAMILY - Rahmayanti, Rahmayanti; Ismaidar, Ismaidar (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Domestic Violence (KDRT) is a problem that often occurs in the family environment, and a classic problem in the legal environment. Domestic violence causes a loss of harmony level in fostering a household. Victims who experience violence have been given legal protection based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence (KDRT), but the issuance of this law is not sufficient to anticipate such violence in the household. Therefore, special attention is needed from the government to protect and provide assistance to victims of violence. From this background, it can be stated that the problem is howways or things that can anticipate the occurrence of violence. The purpose of this research is to find outways that can anticipate the occurrence of domestic violence (domestic violence). This research uses descriptive analytical research method, the approach used is normative juridical. The approach method used in this research is the statutory approach.